Sightings and stranding reports of Fin whales (Balaenoptera physalus) in the Levantine Sea, with recent sightings from Turkey - Stephens, Georgia; Akkaya Bas, Aylin; Hardy, Joseph; Araç, Nilüfer; Lyne, Patrick (J. Cetacean Res. Manage., 2021)
Fin whales (Balaenoptera physalus) are the most commonly observed mysticetes within the Mediterranean Sea, however their status remains vulnerable (VU) and their population in decline mainly due to increasing anthropogenic activities. Sightings of fin whales in the eastern Mediterranean are negligible relative to the central and western basins which eludes to the impression that the eastern Mediterranean provides a less favourable habitat for these cetaceans. This study outlines the sighting and stranding reports of fin whales in the Levantine Basin, the latest of which (an opportunistic sighting of four sub-adults off the coast of Anamur, Turkey in March, 2019) demonstrates the continued presence of this species in the eastern Mediterranean. The current report highlights the need for increased targeted survey effort and collaborative research between neighboring waters to enhance our understanding of the population status of this vulnerable species and aid in the implementation of the necessary conservation actions that are long-missing.